Multibeam bathymetry processed data (KONGSBERG EM712 working area dataset) of RV HEINCKE during cruise HE622, extquotesingleTiefe Rinne extquotesingle at Heligoland, North Sea - Mareike Keller; Jochen Mohrmann; Julian B Stauffer; Sophie Baban (PANGAEA, 2025)
Multibeam bathymetry processed data (KONGSBERG EM712 multibeam echosounder) was collected onboard RV HEINCKE during cruise HE622 in the German North Sea (2023-06-06 - 2023-06-20) at extquotesingleTiefe Rinne extquotesingle at Helgoland. The raw data (.all format) were processed using QPS Qimera software (v 1.7), based on the following workflow: 0.Raw data > 1.Apply correct Sound Velocity Profiles -> 2.Create dynamic surface (shallow Mode) -> 3.Apply Spline Filter (Medium/Weak) > 4. Finalize with manual 2D and 3D editing, -> 5.Export in GeoTIFF format and projected in the UTM32N coordinate system (EPSG:32632). The bathymetry dataset here is gridded at 2 m resolution. The data products were created in the context of the DAM (German Marine Research Alliance), CONMAR research project.